(untitled) (Economic and Political Thought, 2014)
A town may be considered to create a system of common resources, providing living space, jobs and other factors in life quality for its dwellers. Fair and efficient management of these resources requires a specific type of management. According to the findings of E. Ostrom et al., the description of the urban system goes beyond the dichotomy between market and public goods; and the dichotomy between market mechanisms and the public sector and their unreliability does not make it possible to provide optimal effects. This mainly results from a specific character of the goods themselves, as well as a town as a complex system with strong external effects. This applies to the character of urban land management in particular. The current paper proposes the analysis of urban space as common pool resources (CPR). The barriers and potential failures to implement Ostrom’s theory to urban management have been presented, as well as the potential for choosing this theory as an alternative both to commercialization and centralization. The importance of the role of local self-government in negotiating, monitoring and supervising the rules of CPR’s use has also been described.